Effect of Nurse’s Personal Income on Work-family Conflict Amongst Nurses in Selected Hospitals within Nairobi Metropolitan Area, Kenya (African Multidisciplinary Journal of Research, 2022)
Globally, work-family conflict as studied by researchers all over the world from different disciplines is presented as a societal concern. The purpose of this research was to asses’ effect of nurse’s personal income on work and family conflict amongst nurses working in hospitals within Nairobi metropolitan area in Kenya. This study was based on role and conservation of resource theory. The study used descriptive mixed method research design. The population of study was 273 nurses. Choosing of facilities was through purposive sampling according to location and readiness to take part in the study, number of nurses and various services provided, while choosing nurses within the hospital was through stratified random sampling due to different cadres of nurses. A semi structured questionnaire was used to collect both qualitative and quantitative data from the nurses. An interview schedule was used to collect data from directors of nursing services. Quantitative data was analyzed in tables that generated descriptive statistics. Less than 50% of the nurses affirmed that the income has caused conflicts with the family at any point, while 93.5% says salary is not enough for sustaining the family. This means nurses personal income was enough only for the basics. Major categories included: Remuneration challenges (financial constraints and lack of remuneration), and secondly effects of inadequate salary (entrepreneurial opportunities and financial management). The study recommends integration of role theory and conservation of resource theory in reducing negative effect of nurse’s income with work-family conflict. The study also recommends the role played by the organization in reviewing nurses’ salary with a clear policy well understood, effective communication, and training on entrepreneur and management of funds. Overtime allowance to be incorporated as this will motivate nurses and minimize nurse turnover. Family support and understanding to save and do less stressful business that will enable quality family time.Keywords: Nurses, personal income, work-family conflict, financial constraints, job turnover